Implementasi Kebijakan Retribusi Parkir Dalam Menunjang Pendapatan Asli Daerah (Studi di Dinas Perhubungan, Kebudayaan, Pariwisata, Komunikasi dan Informasi Kota Kotamobagu) - Labaeni, Rahmat; Posumah, Jhonny Hanny; Pangkey, Masje Silija (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Retribution is a source of revenue that is relied upon by the Government Kotamobagu, such asparking fees consisting of a special levy parking lot (Regulation 2 of 2008) and levy a parking lot on theedge of the public road (Regulation 6 of 2011). In connection with the study is to examine how theimplementation of policies in the parking levy increase revenue; and the extent to which the results of theimplementation of policies that parking fees in increasing PAD Kotamobagu. This research usesqualitative descriptive method. Location of the study is the Department of Transportation, Culture,Tourism, Communications and Information Kotamobagu City. Informants research as many as 12 peopleconsisting of: head office, secretarial services, head of the section heads, staff / implementers, head UPTDParking, and postal clerk parking. Instruments in this study is the researchers themselves, while collectingdata using interview techniques and assisted technical documentation. Data analysis was performed usingqualitative analysis interactive model of Miles and Hubernann. The results showed: (1) The process ofpolicy implementation parking fees in general are quite effective viewed from four important aspects of theprocess of policy implementation as suggested by Edward III, namely: communication, resources,disposition, and a bureaucratic structure. (2) Implementation of policies levies Parking quite effectiveresults seen from the realization of revenue targets and the development of revenues over the last fiveyears (2010 s / d in 2014). Results of parking fees were a major contribution levies a special parking place,while for curbside parking space levy general is still relatively small. The research results provide theconclusion that the implementation of parking charges policy has a significant support to the increasingacceptance of PAD Kotamobagu. Based on the conclusions of the study put forward some suggestions asfollows: (1) All the important aspects for the implementation of policies retribuasi park, still needs to beimproved; (2) proceeds parking fees that have been achieved over the last few years can still be improved.Keywords: policy implementation, the levy parker, And Local revenue